1979
DOI: 10.23986/afsci.72006
|View full text |Cite
|
Sign up to set email alerts
|

Renal responses of reindeer to high and low protein diet and sodium supplement

Abstract: The effects of reducing dietary nitrogen and increasing sodium chloride intake on renal function were studied in reindeer in order so elucidate the extent of urea conservation and solute excretion by the reindeer kidney. The fall in plasma urea concentration and urea excretion on the low protein diet was accompanied by a significant reduction in the glomerular filtration rate (GFR) and urine osmolality. The fraction of filtered urea reabsorbed increased. However, the contribution of the fall of the GFR to rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

1982
1982
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
2
13
0
1
Order By: Relevance
“…The losses of both absolute body weight and estimated rumen-free body together with increased plasma urea concentrations during the restriction period, indicated that the animals degraded muscle tissue. This was in accordance to Valtonen (1979), who found that reindeer fed a low protein diet with insufficient energy intake used body protein as an energy source, which resulted in increased plasma urea values. The drop in glucose concentrations and Fig.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The losses of both absolute body weight and estimated rumen-free body together with increased plasma urea concentrations during the restriction period, indicated that the animals degraded muscle tissue. This was in accordance to Valtonen (1979), who found that reindeer fed a low protein diet with insufficient energy intake used body protein as an energy source, which resulted in increased plasma urea values. The drop in glucose concentrations and Fig.…”
Section: Discussionsupporting
confidence: 91%
“…and, together with the small or deficient fat reserves, reflected that our animals did not get excess of energy. Reindeer in group C remained healthy with stable blood metabolites throughout the experiment, and had weight losses similar to those observed for reindeer fed a low protein diet (Valtonen, 1979), but less than for reindeer fed a pure lichen diet (Sletten & Hove, 1990;Aagnes & Mathiesen, 1994;Øksendal, 1994). This indicated that the mixing of shrubs and leaves did increase the protein content of the diet, but only marginally.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations